Border Visions: Identity and Diaspora in Film - Kazecki, Jakub; Ritzenhoff, Karen A.; Miller, Cynthia J. (Rowman & Littlefield Publishers, 2013)
Over the last several decades, the boundaries of languages and national and ethnic identities have been shifting, altering the notion of borders around the world. Borderland areas, such as East and West Europe, the US/Mexican frontera, and the Middle East, serve as places of cultural transfer and exchange, as well as arenas of violent conflict and segregation. As communities around the world merge across national borders, new multi-ethnic and multicultural countries have become ever more common. Border Visions: Identity and Diaspora in Film offers an overview of global cinema that addresses borders as spaces of hybridity and change. In this collection of essays, contributors examine how cinema portrays conceptions of borderlands informed by knowledge, politics, art, memory, and lived experience, and how these constructions contribute to a changing global community. These essays analyze a variety of international feature films and documentaries that focus on the lives, cultures, and politics of borderlands. The essays discuss the ways in which conflicts and their resolutions occur in borderlands and how they are portrayed on film. The volume pays special attention to contemporary Europe, where the topic of shifting border identities is one of the main driving forces in the processes of European unification. Among the filmmakers whose work is discussed in this volume are Fatih Akin, Montxo Armendàriz, Cary Fukunaga, Christoph Hochhäusler, Holger Jancke, Emir Kusturica, Laila Pakalnina, Alex Rivera, Larissa Shepitko, Andrea Staka, Elia Suleiman, and István Szabó. A significant contribution to the dialogue on global cinema, Border Visions will be of interest to students and scholars of film, but also to scholars in border studies, gender studies, sociology, and political science.